2015
DOI: 10.1021/acs.est.5b01090
|View full text |Cite
|
Sign up to set email alerts
|

Potential Health Impact of Environmentally Released Micro- and Nanoplastics in the Human Food Production Chain: Experiences from Nanotoxicology

Abstract: High concentrations of plastic debris have been observed in the oceans. Much of the recent concern has focused on microplastics in the marine environment. Recent studies of the size distribution of the plastic debris suggested that continued fragmenting of microplastics into nanosized particles may occur. In this review we assess the current literature on the occurrence of environmentally released micro- and nanoplastics in the human food production chain and their potential health impact. The currently used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
455
0
27

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 969 publications
(486 citation statements)
references
References 147 publications
(367 reference statements)
4
455
0
27
Order By: Relevance
“…Therefore, food products may represent an important route of entry for MPs into humans, although systematic quantitative data of MPs in human tissues have not been reported. Furthermore, several studies have observed MPs in some non-marine food products, such as honey (40–660 items/kg honey), sugars (32 ± 7 items/kg sugar), beer (12–109 items/L beer) and table salt (7–681 items/kg salts)35. These represent additional dietary routes for human populations to be exposed to MPs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, food products may represent an important route of entry for MPs into humans, although systematic quantitative data of MPs in human tissues have not been reported. Furthermore, several studies have observed MPs in some non-marine food products, such as honey (40–660 items/kg honey), sugars (32 ± 7 items/kg sugar), beer (12–109 items/L beer) and table salt (7–681 items/kg salts)35. These represent additional dietary routes for human populations to be exposed to MPs.…”
Section: Discussionmentioning
confidence: 99%
“…Clear parallels 811 exist from this work to future studies with nanoparticles, with collaboration between the disciplines 812 likely to improve understanding (Bouwmeester et al, 2015;Syberg et al, 2015). This takes the more 813 environmentally relevant approach that it is necessary to understand the fate, behaviour and impacts 814 of microplastics as an environmental pollutant and, therefore, their potential implications for keys 815 ecosystem components and processes.…”
Section: Conclusion 802mentioning
confidence: 98%
“…Increasing amounts of small plastic debris build up in natural systems mainly due to the gradual breakdown of larger plastics such as disposable packaging materials by weathering and photodegradation (Ivar Do Sul and Costa 2014;Bouwmeester, Hollman, and Peters 2015). The contamination of microplastics (< 1 um) in aquatic ecosystems is detected worldwide, even in remote areas (Hammer, Kraak, and Parsons 2012;Cozar et al 2014;Eerkes-Medrano, Thompson, and Aldridge 2015), since most plastics are not biodegradable and remain in suspension due to lower density than water.…”
Section: Introductionmentioning
confidence: 99%